2002
DOI: 10.1161/hc0702.104127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Autonomic Blockade on T-Wave Alternans in Humans

Abstract: Background-T-wave alternans (TWA) is an important noninvasive measure of ventricular arrhythmia vulnerability. This study tested the hypothesis that the autonomic nervous system influences TWA measurement in high-risk subjects with coronary artery disease. Methods and Results-T-wave alternans was measured in 60 patients with coronary artery disease, left ventricular dysfunction, and inducible sustained ventricular tachycardia during electrophysiological studies. All patients had TWA measured at baseline with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 37 publications
7
86
0
2
Order By: Relevance
“…Studies in dogs and humans show that ␤-blockers suppress TWA, suggesting an etiological role for the sympathetic nervous system (3,10,11,20), although, conversely, isoproterenol may not consistently elevate TWA during constant pacing (8). Compared with baseline in our study, dogs at peak infusion exhibited sinus tachycardia, reduced total spectral power of HRV that, over 10 min, is analogous to SD of normal R-wave-to-R-wave interval and primarily reflects VLF power and nonsignificant trends for an elevated ratio of LF to HF frequency power.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dogs and humans show that ␤-blockers suppress TWA, suggesting an etiological role for the sympathetic nervous system (3,10,11,20), although, conversely, isoproterenol may not consistently elevate TWA during constant pacing (8). Compared with baseline in our study, dogs at peak infusion exhibited sinus tachycardia, reduced total spectral power of HRV that, over 10 min, is analogous to SD of normal R-wave-to-R-wave interval and primarily reflects VLF power and nonsignificant trends for an elevated ratio of LF to HF frequency power.…”
Section: Discussionmentioning
confidence: 99%
“…Anger and emotional distress may precede arrhythmic episodes in a substantial number of individuals, 16,17,34,35 and controlled laboratory stress tasks can be used to assess susceptibility to electrophysiological markers of arrhythmic vulnerability. TWA is predictive of future arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenergic and autonomic nervous system pathways are involved in exercise-induced 33,34 and mental stress-induced 21 TWA. Patients tested while using ␤-blockade (nϭ13) had similar TWA responses to mental stress as patients tested without ␤-blockade but displayed attenuated TWA levels during rest (Pϭ0.03) and exercise (Pϭ0.02).…”
Section: Pathophysiological Mechanisms Of Mental Stress-induced Twamentioning
confidence: 99%
“…18 Various studies have examined the influence of basal autonomic activity on TWA. Although those studies indicated that using β-blockers and amiodarone decreases the magnitude of TWA, as well as the parameters of HRT, [22][23][24][25][26] their use did not interfere with the ability of TWA to assess the risk for arrhythmic events. 21 Similarly, this finding may also be confirmed in our study.…”
Section: Mma-based Twamentioning
confidence: 98%